Rapid next-generation sequencing-based diagnostics of bacteremia in septic patients - Grumaz, Christian; Hoffmann, Anne; Vainshtein, Yevhen; Kopp, Maria; Grumaz, Silke; Stevens, Philip; Decker, Sebastian; Weigand, Markus A.; Hofer, Stefan; Brenner, Thorsten; Sohn, Kai (The journal of molecular diagnostics, 2020)
The increasing incidence of bloodstream infections including sepsis is a major challenge in intensive care units worldwide. However, current diagnostics for pathogen identification mainly depend on culture- and molecular-based approaches, which are not satisfactory regarding specificity, sensitivity, and time to diagnosis. Herein, we established a complete diagnostic workflow for real-time high-throughput sequencing of cell-free DNA from plasma based on nanopore sequencing for the detection of the causative agents, which was applied to the analyses of eight samples from four septic patients and three healthy controls, and subsequently validated against standard next-generation sequencing results. By optimization of library preparation protocols for short fragments with low input amounts, a 3.5-fold increase in sequencing throughput could be achieved. With tailored bioinformatics workflows, all eight septic patient samples were found to be positive for relevant pathogens. When considering time to diagnosis, pathogens were identified within minutes after start of sequencing. Moreover, an extrapolation of real-time sequencing performance on a cohort of 239 septic patient samples revealed that more than 90% of pathogen hits would have also been detected using the optimized MinION workflow. Reliable identification of pathogens based on circulating cell-free DNA sequencing using optimized workflows and real-time nanopore-based sequencing can be accomplished within 5 to 6 hours following blood draw. Therefore, this approach might provide therapy-relevant results in a clinically critical timeframe.
Gesehen am 23.04.2020